2020
DOI: 10.1080/21870764.2020.1847425
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic influence of SiC and C3N4 reinforcements on the characteristics of ZrB2-based composites

Abstract: In this work, ZrB 2-SiC and novel C 3 N 4-doped ZrB 2-SiC composites were manufactured at 1850° C under an external load of 40 MPa for 6 min via spark plasma sintering. The effects of C 3 N 4 on the mechanical characteristics (flexural strength, Vickers hardness, and fracture toughness) and microstructure of the ZrB 2-SiC-based composites were investigated. By adding 5 wt% g-C 3 N 4 , a fully dense ceramic composite was fabricated, compared to the C 3 N 4-free ZrB 2-SiC composite with a relative density of 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The mechanical properties also have been improved by adding 5 wt% C 3 N 4 to the ZrB 2 matrix, due to densification enhancement and grain growth reduction. The Vickers hardness, fracture toughness, and flexural strength have been increased from 10.1 GPa, 1.9 MPam ½ , and 187.6 MPa to 16.2 GPa, 5.4 MPam ½ , and 516.4 MPa, respectively [33].…”
Section: Sintering Aid and Reinforcement Phase In Compositesmentioning
confidence: 95%
“…The mechanical properties also have been improved by adding 5 wt% C 3 N 4 to the ZrB 2 matrix, due to densification enhancement and grain growth reduction. The Vickers hardness, fracture toughness, and flexural strength have been increased from 10.1 GPa, 1.9 MPam ½ , and 187.6 MPa to 16.2 GPa, 5.4 MPam ½ , and 516.4 MPa, respectively [33].…”
Section: Sintering Aid and Reinforcement Phase In Compositesmentioning
confidence: 95%
“…36 Similarly, studies on silicon carbide and carbon nitride composite catalysts have been reported, mainly including g-C 3 N 4 -SiC-Pt, 37 ZrB 2 -SiC/C 3 N 4 . 38 Its applications mainly include the degradation of wastewater such as rhodamine B, alizarin red, and tetracycline, photocatalytic hydrogen production, and the construction of pressure-resistant materials. However, the SiC used in previous research reports are all commercial micro- or nano-powders, and its crystal form is a mixed crystal phase of α-SiC and β-SiC.…”
Section: Introductionmentioning
confidence: 99%
“…(Zr,Ti)B 2 -(Zr,Ti)N ceramic composite is fabricated due to the in-situ synthesis and penetration of ZrN and TiB 2 as the result of TiN addition to the ZrB 2 ceramic and their chemical reactions during the spark plasma sintering [40]. The Appearance of insitu synthesized h-BN, the solid solution of (Zr,Ti)B 2 , and ZrN as well as ZrO 2 was proved in TiN-doped ZrB 2 -SiC leading to mechanical properties improvement [41].…”
Section: Introductionmentioning
confidence: 99%